EFFECT OF CHANGES IN SOIL CATION EXCHANGE CAPACITY ON THE RECLAMATION OF LEAD BY ELEUSINE INDICA (L.) GAERTN (FUDMA JOURNAL OF SCIENCES, 2023)
Contamination of soil by various heavy metals such as lead poses a serious environmental problem. Lead (Pb) is one of the harmful and frequently encountered heavy metals that is uptake by plants. Cation Exchange Capacity (CEC) is one of the important factors influencing metal uptake and accumulation. Rate of this uptake causes a number of toxic symptoms in plants. This study was carried out to evaluate the effect of changes in CEC on accumulation of lead by Eleusine indica. Seven soil CEC ratios were obtained by mixing clay (C) and humus (H) soils (C, 90C:10H, 75C:25H, 50C:50H, 25C:75H, 10C:90H, H) in two replicates. The soil was polluted with 675.2mg/kg of Pb and Eleusine plants were transplanted into the 5kg soil. Results showed that CEC of the soils influenced the accumulation of Pb in the root of test plant. Highest CEC (0.710 meq/L) was obtained in the H soil with highest Pb root uptake (29.5mg/kg), while the lowest CEC (0.210 meq/L) was obtained in C soil with low Pb root uptake (12.5mg/kg). The CEC was observed to increase with addition of H ratio. Significant reduction (P
Keywords: Soil cation exchange capacity, Reclamation, Lead, Eleusine indica